2015
DOI: 10.1557/adv.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

All-Printed Transistors on Nano Cellulose Substrate

Abstract: We report fully-printed top-gate-bottom-contact organic thin-film transistors using substrates prepared from cellulose nanofibers and commercially available printing inks to fabricate the devices. Gravure printing was used to coat the substrate with a polymer resist to decrease the surface roughness and close the surface. Transistor structures were fabricated using inkjet printing for conductors and gravure prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Besides using nanopapers for two-dimensional reinforcement in composites [25,26], NC in the form of dense fibre networks, e.g. cellulose nanopapers [27], is also an important material for various advanced applications, including filtration membranes [28][29][30], packaging [31] and substrates for flexible, printed electronics [32]. Thereby, the ability to design [33], tailor and engineer the physical properties of nanopapers is of upmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides using nanopapers for two-dimensional reinforcement in composites [25,26], NC in the form of dense fibre networks, e.g. cellulose nanopapers [27], is also an important material for various advanced applications, including filtration membranes [28][29][30], packaging [31] and substrates for flexible, printed electronics [32]. Thereby, the ability to design [33], tailor and engineer the physical properties of nanopapers is of upmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…These headways of green innovation, minimal-effort paper substrates, and solutionbased natural thin film transistors are promising for use in the future for adaptable devices application [275]. In another study, Hassinen et al [276] revealed entirely printed top-gate bo om-contact natural paper transistors by utilizing substrates arranged from CNFs and monetarily accessible printing inks to create the gadgets. Gravure printing was used to coat the substrate with a polymer instead of diminishing the surface harshness and closing the surface.…”
Section: Paper Transistormentioning
confidence: 99%
“…The introduction of CNFs delayed the degradation of the EVA film via deacetylation while retaining the EVA film's visible light transparency of above 75%. In another study, Hassinen et al [276] revealed entirely printed top-gate bottomcontact natural paper transistors by utilizing substrates arranged from CNFs and monetarily accessible printing inks to create the gadgets. Gravure printing was used to coat the substrate with a polymer instead of diminishing the surface harshness and closing the surface.…”
Section: Solar Cellsmentioning
confidence: 99%
“…As electronics are moving toward being inexpensive, flexible, lightweight, environmentally friendly, biodegradable, or even biocompatible, the interest in the fabrication of electronics on inexpensive and flexible opaque and hazy cellulose substrates has renewed. [38,114,120,121] With the emergence of advanced electronic materials, for instance, π-conjugated organic molecules and polymers, graphene, carbon nanotubes (CNTs), and silver nanowires (Ag NWs)/nanoparticles, opaque and hazy cellulose substrate is considered a perfect platform for integrating with these functional materials through advanced manufacturing techniques (e.g., supercalendering, [113] inkjet printing, [122][123][124] and 3D printing [117] ) to prepare multifunctional substrate for a wide range of electronic applications.…”
Section: Opaque and Hazy Cellulose Substratesmentioning
confidence: 99%